THE EFFECT OF THE GROUP WORK STRATEGY ON ACQUIRING HISTORICAL CONCEPTS AND DEVELOPING CREATIVE THINKING SKILLS IN HISTORY FOR FOURTH YEAR MIDDLE SCHOOL STUDENTS (American Journal of Research in Humanities and Social Sciences, 2024)
The research explores the impact of the group work strategy on the acquisition of historical concepts and the development of creative thinking skills for fourth-year middle school students in history. The research indicates the importance of developing creative thinking skills and understanding historical concepts among students in the middle school stage. The effect of using group work as a teaching strategy in stimulating students' creative thinking and enhancing their understanding of historical concepts is analyzed.The research is systematically studied using a field experiment that includes a group of students who learn history through a group work strategy compared to another group that follows traditional methods. The development of history concepts and creative thinking skills of students in both groups is assessed using approved assessment tools and scales.The results indicate that the use of group work leads to a significant improvement in the acquisition of historical concepts and the development of students’ overall creative thinking skills compared to traditional methods of learning. The research also demonstrates some mechanisms through which the effectiveness of the group work strategy in improving students' learning experience in history can be enhanced.